Efektivitas Penggunaan Puzzle Sebagai Media Pembelajaran Bahasa Ekspresif Usia 5-6 Tahun - Andini, Shaqina; Darwin Effendi2; Dessi Andriani (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to determine the effectiveness of using puzzles as a learning medium for expressive language for 5-6 year olds at Wijaya Kusuma Kindergarten, Palembang. The results of observations at Wijaya Kusuma Kindergarten show that the learning media used are still less innovative and have not been able to attract children's interest in learning actively. Learning activities that tend to be monotonous make children passive so that the development of children's expressive language has not developed properly. This type of research is experimental research, namely pre-experimental type One-Group Pretest-Posttest Design by providing treatment in the form of puzzles to children, then comparing children's expressive language abilities before and after being given puzzles. The sample used in this study was class B1, totaling 16 children. The method of collecting research data used a checklist observation sheet. The method in analyzing research data is by using the paired sample T test. The results of the study based on the paired sample T test can be tcount> ttable or 32.940> 1.753 that Ho is rejected and Ha is accepted. It can be concluded that there is a significant influence of 0.000 which is smaller than 0.05, stating that the effectiveness of using puzzle media as a medium for expressive language learning for 5-6 year olds at Wijaya Kusuma Kindergarten, Palembang.